Antibacterial effectiveness of a second generation steam pasteurization™ system for beef carcass decontamination - A. Truax; S. Sporing; S.A. Rueger; M. Schafer; L.K. Bohra; L. Harris; Randall K. Phebus; Deanna D. Retzlaff (Kansas Agricultural Experiment Station Research Reports, 1999)
The original commercial Steam Pasteurization ™ System (SPS 400) involved a sealable moving car by which carcass sides were carried through the steam chamber at standard line speeds. A second generation "static chamber" system (SPS 400-SC) eliminates the mechanical moving car and has been installed in a large beef slaughter facility. We collected data to verify SPS 400-SC's effectiveness at chamber temperatures from 185 to 205EF in a batch process mode (only test carcasses passing through the unit at variable intervals to facilitate collection of research samples) and at 190EF with the system running continuously. Tissue samples were obtained from different carcass anatomical locations to evaluate the uniformity of thermal treatment. Batch-type steam treatment at 185 and 190EF did not consistently produce significant bacterial reductions on the five anatomical locations sampled. Batch processing at 195, 200, and 205EF provided increasingly greater total bacterial reductions, ranging from 1.0 to 2.0 log colony forming units (CFU)/cm2. Under continuous operation at 190EF, typical of commercial operation, total bacterial reductions at the carcass midline averaged 1.6 log CFU/cm2. The new SPS design is substantially simplified in terms of moving components and should offer highly efficient operation and less mechanical upkeep, extremely important in Hazard Analysis Critical Control Point (HACCP) programs, which require assurance of virtually 100% system operation. The new SPS 400-SC design will provide beef processors a very effective and reliable means of assuring that microbiologically clean carcasses enter the holding cooler, thus substantially reducing the risk of pathogenic contamination.
Keywords: Cattlemen' s Day; 1999; Kansas Agricultural Experiment Station contribution; no. 99-339-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 831; Beef; Steam pasteurization; Beef carcass decontamination; Antibacterial